ANALISIS KELAYAKAN USAHA INDUSTRI TEMPE DI KECAMATAN TERUSAN NUNYAI KABUPATEN LAMPUNG TENGAH - Riki Muhammad; Marlinda Apriyani; Fadila Marga Saty; Dayang Berliana (Universitas Galuh, 2023)
This study aims to describe the business of the tempe industry, the financial feasibility of the tempe industry, and the sensitivity of the tempe industry in the Terusan Nunyai District, Central Lampung Regency. This research was conducted from December 2021 to September 2022. Sampling using sampling, namely taking several samples in a group and using a structured questionnaire as the main data collection tool to obtain specific information and the number of respondents was 3 industries . Data analysis uses financial analysis and sensitivity analysis. The results showed that the production process for the tempe home industry went through several stages, namely peeling, washing, boiling, fermenting, and packaging. The Tempe Industry in the Terusan Nunyai District which is currently being implemented is said to be financially feasible because based on the investment criteria it is above the maximum feasibility limit. This can be shown by the Net Present Value (NPV) of Rp. 125,786,982, Internal Rate of Return (IRR) of 37%, Net B/C ratio with a value of 1.99, Break Even Point (BEP) that is for 4 years 7 months 1 day and Payback Period (PBP) for 4 months 20 days. The sensitivity analysis shows that the tempe home industry is proven to be insensitive to changes from an increase in raw material costs and a decrease in revenue of 4.5% for the tempe home industry. The result of these changes is that all investment criteria still meet the criteria, so that home industries are still feasible to run.